Analisis Wacana Kritis pada Berita Pemilihan Walikota Makassar Sebagai Bentuk Pendidikan Politik dan Perannya dalam Pembelajaran Membaca Kritis bagi Siswa - Wahyuni Wahyuni; Akmal Hamsa; Ramly Ramly (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze the language features in the news of the 2020 Makassar Mayor election as a form of political education and its role in critical reading learning for students. The research method used is descriptive method with a qualitative approach. Data collection techniques using documentation, reading, and recording. The data analysis technique used is Norman Fairclough's critical discourse analysis model through procedures for identifying data, classifying data, analyzing data, and drawing conclusions. The results of the study show that the language of power as a tool of power through linguistic features and has been used optimally by those who have the intention to power. This can be seen in the efforts to depict the image of the candidate pair, the delivery of the vision and program, as well as campaign activities and visits by the candidates. Through this identification, it appears that each candidate pair exercises its power in presenting the text to the reader. Through this critical discourse analysis of news, it can improve students' critical reading skills in responding to various texts in the mass media as a form of political education.